2015
DOI: 10.1111/1440-1681.12329
|View full text |Cite
|
Sign up to set email alerts
|

Original and generic latanoprost for the treatment of glaucoma and ocular hypertension: Are they really the same?

Abstract: We compared the intraocular pressure (IOP)-lowering effect and safety profile of latanoprost (Xalatan) with its generic variant, Glautan (Unipharm, Tel Aviv, Israel). After 1 and 4 weeks of treatment, a randomized, prospective, cross-over comparison was carried out that included patients with open-angle glaucoma or ocular hypertension, either naïve or treated and well-controlled, who were attending the Department of Ophthalmology, Tel Aviv Medical Centre, Tel Aviv, Israel, between May 2010 and November 2012. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…The main limitation is the small sample size. Nonetheless, the previous studies that found a difference between the generic latanoprost 0.005% ophthalmic solution and the reference drug had even smaller populations 18,19. Additionally, although we can draw some conclusions regarding ALT, we cannot extrapolate those findings to other generic formulations not used in this study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The main limitation is the small sample size. Nonetheless, the previous studies that found a difference between the generic latanoprost 0.005% ophthalmic solution and the reference drug had even smaller populations 18,19. Additionally, although we can draw some conclusions regarding ALT, we cannot extrapolate those findings to other generic formulations not used in this study.…”
Section: Discussionmentioning
confidence: 69%
“…All these considered, there are few studies evaluating different types of populations that previously assessed generic formulations of latanoprost 0.005% ophthalmic solution versus XLT regarding IOP-lowering effect and safety profile, and the results are conflicting. Considering the studies that found a better performance for XLT when compared to the generic formulation, Golan et al18 found a tendency for better IOP control for XLT when compared to Glautan (an Israeli generic formulation) in a population of 19 POAG and HO patients at 1-month follow-up and Narayanaswamy et al19 found XLT to have better IOP control than Latoprost (an Indian generic formulation) in a population of 30 POAG and HO patients at a 24-week crossover protocol. On the other hand, considering the studies that found no difference between XLT and the generic formulation, Diagourtas et al20 found no difference between two Greek latanoprost 0.005% formulations (Latz and Xalaprost) and XLT in a 60 POAG and OH patients 16-week trial and Digiuni t al,14 found no difference between an Italian latanoprost 0.005% formulation (manufactured by Mipharm) and XLT in a 184 POAG and OH patients 12-week trial.…”
Section: Discussionmentioning
confidence: 99%
“…A large double-masked study of 184 patients in Italy found noninferiority of generic latanoprost to Xalatan, with no difference in adverse events [15]. Similarly, Golan and colleagues conducted a randomised crossover study comparing Xalatan and a generic latanoprost, with patients masked to the medication they were receiving [16]. ere were no significant differences in IOP lowering between groups but more ocular surface disease-type side effects were reported when using the generic.…”
Section: Efficacymentioning
confidence: 99%
“…Израильские исследователи провели рандомизированное проспективное перекрестное исследование для сравнения эффективности ксалатана и его дженерика глаутана (Glautan, Unipharm, Тель-Авив, Израиль) [12]. Ксалатан имел тенденцию к большей эффективности, чем глаутан, через неделю и через месяц после начала лечения, но разница не была статистически значимой.…”
Section: Issues Of Safety and Efficacy Of Drugs Attracts Much Attentiunclassified